Inverting substitution patterns on amphiphilic cyclodextrins induces unprecedented formation of hexagonal columnar superstructures. Issue 36 (2nd August 2017) - Champagne, Pier-Luc; Ester, David; Zeeman, Michael; Zellman, Carson; Williams, Vance E.; Ling, Chang-Chun
Abstract : Inverting the substitution patterns of amphiphilic cyclodextrins has uncovered their unprecedented abilities to form hexagonal columnar mesophases. Abstract : Cyclodextrins (CDs) constitute a unique class of macrocycles that possess a truncated cone-shaped cavity. Chemical modifications with simple hydrophobic groups can generate amphiphilic derivatives capable of self-assembling into thermotropic liquid crystals. Without the help of introduced mesogenic functionalities, almost all known amphiphilic CDs form smectic mesophases. Here we report that by inverting the substitution patterns of β-CD derivatives modified with simple hydrophobic chains and oligoethylene (OEG) groups, it is possible to transform the nature of their self-assembly from smectic to columnar thermotropic liquid crystalline phases. This investigation reveals some intriguing properties of CD scaffolds as a unique class of host mesogens. Multi-highly ordered channels were found in the formed hexagonal columnar mesophases that could find potential applications in different fields such as ion transport and conductivity.